2021
DOI: 10.1016/j.jsat.2021.108374
|View full text |Cite|
|
Sign up to set email alerts
|

Identifying the impacts of the COVID-19 pandemic on service access for people who use drugs (PWUD): A national qualitative study

Abstract: Introduction: Closures and reductions in capacity of select health and social services in response to the COVID-19 pandemic may have placed people who use drugs (PWUD) at a disproportionately increased risk for experiencing harms, and resulted in critical treatment disruptions. We conducted the current national study among a cohort of PWUD to understand how COVID-19 has affected service access, including any significant impacts PWUD may have experienced. Results will contribute to the evidence base for informi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
100
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(119 citation statements)
references
References 50 publications
13
100
0
1
Order By: Relevance
“…Our results are similar to COVID-19-related changes in drug use and outcomes reported elsewhere [5,6,[18][19][20]. Some participants discussed changes in the kind of substances they use and their purchasing habits using during COVID-19 due to border closures, inability to access certain drugs, or changes in drug prices, which was previously anticipated [5].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results are similar to COVID-19-related changes in drug use and outcomes reported elsewhere [5,6,[18][19][20]. Some participants discussed changes in the kind of substances they use and their purchasing habits using during COVID-19 due to border closures, inability to access certain drugs, or changes in drug prices, which was previously anticipated [5].…”
Section: Discussionsupporting
confidence: 89%
“…Some participants discussed changes in the kind of substances they use and their purchasing habits using during COVID-19 due to border closures, inability to access certain drugs, or changes in drug prices, which was previously anticipated [5]. Many participants accessed supervised consumption and overdose prevention sites less frequently due to closures or long wait times as a result of physical distancing requirements, consistent with prior research [5,6,19,20]. Our results suggest that physical distancing recommendations and the inability to access safe spaces has created situations where individuals used drugs less safely.…”
Section: Discussionsupporting
confidence: 68%
“…This may be due to rapid changes to assertive outreach and NSP home delivery, which were well received and cited as addressing barriers to accessing equipment in pharmacies. These changes may have reduced accessibility issues which have emerged in recent North American research ( Russell et al, 2021 ). Research from jurisdictions where NSP home delivery was not possible identified this as a barrier to treatment access ( Seaman et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…28 For example, prescribers were given increased discretion to provide extended takehome supplies ('carries') of OAT medications and permitted to prescribe OAT over the phone. 29 These measures improved OAT continuity and, despite initial concerns of sharing or improper dosing of OAT medications, there is no evidence that they increased the risk of harm to patients or communities. 30 Use a harm reduction approach to OAT by relaxing entry and management criteria.…”
Section: Ensure Opioid Agonist Therapy (Oat) Access Options and Continuitymentioning
confidence: 99%
“…17 These changes may impact PWUD in several ways including reduced tolerance due to an inability to access opioids or using unregulated fentanyl that also contains nonprescription benzodiazepines. 29,37 A strong evidence base for injectable OAT exists and programs are currently available in three provinces. 32,38 High dose injectable hydromorphone is currently not covered by the Ontario Drug Benefit, and adding it to the formulary would increase available treatment options.…”
Section: Facilitate Adaptive Harm Reduction Strategiesmentioning
confidence: 99%